Identifying Student Misconceptions About Guidance Counseling in Schools - Badri, Nurmaya; Lesmana, Gusman; Fatanah, Amrina (Lembaga Riset Mutiara Akbar, 2023)
Misconceptions are incorrect explanations and ideas that are inconsistent with scientific understanding accepted by experts. Misconceptions often occur because the concepts learned and accepted by students are different. The purpose of this study was to find out how the misconceptions about guidance and counseling services at SMP Muhammadiyah 16 Lubuk Pakam and SMP Muhammadiyah 16 Lubuk Pakam. Data analysis techniques in this study used descriptive analysis with frequency distribution techniques. Articles in this literature review use research articles that contain observations, in which there are abstractions, introductions, discussions and conclusions. The results of this study explain that misconceptions about guidance and counseling services at SMP Muhammadiyah 16 Lubuk Pakam still occur because the teacher who serves as a counseling teacher is not a counseling teacher, but a graduate of Sociology who is given the responsibility to solve student problems. Counseling services and program implementation have started well because the counseling teachers are able to carry out their duties in carrying out counseling services in accordance with the operational guidelines for the implementation of guidance and counseling for junior high schools (SMP Muhammadiyah 16 Lubuk Pakam)